Comparison of nutritional outcomes and complication profiles of commercial enteral nutrition and homemade homogenate in patients with dysphagia who are chronically immobilized - Liu, Xuanwei; Tan, Lihua; Liang, Yeji; Wang, Xiaoman; Liu, Yu; Pang, Tao; Zhao, Nana (Frontiers in Nutrition, 2026)
ObjectiveThe aim of this study was to compare the nutritional outcomes and complications associated with homemade homogenate administered via nasogastric tube vs. a commercially available enteral nutrition formula in patients with dysphagia who are chronically immobilized.MethodsIn a prospective randomized controlled trial, 135 patients were allocated to receive either homemade homogenate (n = 67) or commercial enteral nutrition (n = 68). All patients received equivalent pharmacological and rehabilitative interventions. Nutritional indicators, including albumin, prealbumin, hemoglobin, body mass index, mid-arm circumference, calf circumference, arm muscle circumference, triceps skinfold thickness, and Nutritional Risk Screening 2002 (NRS2002), were assessed on days 1, 30, and 45 following admission. The incidence of complications, including pulmonary infections, gastrointestinal adverse reactions, and pressure ulcers, was recorded. Microbial colony counts were assessed in samples of homemade homogenate. Data were analyzed using independent-sample t tests and chi-squared tests.ResultsBy day 45, patients in the commercial formula group exhibited significantly greater improvement in serum and anthropometric nutritional indices compared to those in the homemade homogenate group. NRS2002 scores decreased more substantially in the commercial formula group at days 30 and 45. This group also experienced a lower incidence of pulmonary infections, gastrointestinal symptoms, and pressure ulcers. Among 15 samples of homemade homogenate, 4 exceeded the acceptable microbial colony count. Additionally, the homemade formula was lower in macro- and micronutrients and higher in sodium compared to the commercial preparation.ConclusionCommercial enteral nutrient solution demonstrated superior efficacy in improving nutritional status and reducing complications in patients with dysphagia and prolonged immobility. Although homemade homogenate may be considered in resource-constrained settings, it requires careful formulation, enhanced hygienic preparation, and standardized storage protocols to ensure safety and nutritional adequacy.